2021
DOI: 10.3390/metabo11120878
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fermentation of Low or High Tannin Fava Bean-Based Diets on Glucose Response, Cardiovascular Function, and Fecal Bile Acid Excretion during a 28-Day Feeding Period in Dogs: Comparison with Commercial Diets with Normal vs. High Protein

Abstract: We have shown that feeding dogs fava bean (FB)-based diets for 7 days is safe and FB flour fermentation with Candida utilis has the potential to decrease FB anti-nutritional factors. In the present study, the effects of 28-day feeding of 4 different FB-based test dog foods containing moderate protein (~27% dry matter (DM)) were compared with two commercial diets with normal protein (NP, grain-containing, ~31% DM protein) or high protein (HP, grain-free, ~41% DM protein). Health parameters were investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 54 publications
4
8
0
Order By: Relevance
“…Total bilirubin and indirect bilirubin were also seen to decrease in the pulse-inclusive diets, the cause for this however remains unknown. The current study in Beagles observed increases in serum phosphorus after feeding the lentil-based diet which agrees with a previous 28-day study in adult Labrador retrievers fed a diet high in both peas and lentils as well as 7-and 28-day studies in Beagles fed a commercial pulse-containing diet [ 15 , 41 , 42 ]. However, in the current study RBC counts were similar after feeding all three lab-made diets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Total bilirubin and indirect bilirubin were also seen to decrease in the pulse-inclusive diets, the cause for this however remains unknown. The current study in Beagles observed increases in serum phosphorus after feeding the lentil-based diet which agrees with a previous 28-day study in adult Labrador retrievers fed a diet high in both peas and lentils as well as 7-and 28-day studies in Beagles fed a commercial pulse-containing diet [ 15 , 41 , 42 ]. However, in the current study RBC counts were similar after feeding all three lab-made diets.…”
Section: Discussionsupporting
confidence: 92%
“…Only a few previous feeding studies examining pulse-inclusive diets have been conducted in healthy dogs or in breeds not known to be susceptible to DCM. Of these, several reported no effect on echocardiography or blood indicators of DCM after feeding laboratory Beagles pea- or fava bean-based diets for only 7 days [ 21 , 41 ] or faba bean based diets for 28-days [ 41 , 42 ]. Also, a clinical trial where a similarly high pea-based diet (60% as fed) was fed for 12-weeks to client-owned dogs of variable breeds reported increased LV diastolic dimensions without a change in stroke volume or cardiac output [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 5 years, microbial-derived BAs have been increasingly studied in canines ( Table 1 ). Studies in healthy dogs have characterized the microbial-derived BAs during the development of puppies [ 114 ], as well as the impact of antimicrobials [ 59 , 115 , 116 , 117 , 118 ] and diet [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ] on the BA pools of healthy dogs. Additional studies on disease states have largely focused on the context of gastrointestinal [ 52 , 64 , 127 , 128 , 129 , 130 , 131 ] and pancreatic disease [ 128 , 132 ], with additional information characterizing microbial-derived BAs in canine obesity [ 119 , 125 ], diabetes mellitus [ 113 ], and myxomatous mitral valve disease (MMVD) [ 133 ].…”
Section: Canine Microbial-derived Bile Acidsmentioning
confidence: 99%
“…Therefore, in healthy dogs, additional multi-omics studies are required to characterize collaborative BA metabolism, specifically describing canine gut microbes mechanistically responsible for BA biotransformations in health. In the following sections, the impact of antimicrobials [ 59 , 115 , 116 , 117 , 118 ] and diet [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ] on the BA pools of healthy dogs will be reviewed.…”
Section: Canine Microbial-derived Bile Acidsmentioning
confidence: 99%
See 1 more Smart Citation